Pengaruh Pemberian Terapi Oksigen Hiperbarik 2,4 ATA terhadap Kadar C-Reactive Protein (CRP) Darah Mencit Model Rheumatoid Arthritis - Thalia Tamara; Hendrata Erry Andisari; Totot Mudjiono (Oceana Biomedicina Journal, 2019)
Background: Rheumatoid Arthritis (RA) is an autoimmune disease with an increasingprevalence from year to year. RA mortality continues to increase in the last 1 decade due tothe absence of effective prevention and therapy. Hyperbaric oxygen therapy can be anadjuvant therapy for Rheumathoid Arthritis.Objective: This study uses Hyperbaric Oxygen Therapy to reduce the inflammatory reactionin patients with Rheumatoid Arthritis.Method: Samples used are 16 male balb/c mice, divided into 2 groups, 1) group of inducedexperimental animals as models of Rheumatoid Arthritis 2) group of induced experimentalanimals as models of Rheumatoid Arthritis and given 3x30 minutes of 2.4 ATA hyperbaricoxygen therapy for 10 consecutive days. On 59th day, ELISA screening test is performed forC-ReactiveProtein measurement.Result: The average results of C-Reactive Protein levels between 2 groups, are, the group ofmice with rheumatoid arthritis model that was not treated with HBO therapy had an averageCRP level of 0.204 Pg / ml, while the group of mice with rheumatoid arthritis model which istreated with HBO therapy has a mean CRP level of 0.113 Pg / ml.Conclusion: There is an effect of hyperbaric oxygen therapy to C-Reactive Protein level inmice with rheumatoid arthritis model.